2012
DOI: 10.1080/07448481.2011.589876
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Use of Prescription Stimulants During College: Four-Year Trends in Exposure Opportunity, Use, Motives, and Sources

Abstract: Objective Examine trends in nonmedical use of prescription stimulants (NPS), including motives, routes of administration, sources, cost, and risk factors. Participants 1,253 college students. Methods Data were collected annually during academic years 2004–5 through 2008–9. Generalized estimating equations analyses evaluated longitudinal trends. Logistic regression models evaluated stability of associations between risk factors and NPS over time. Results Almost two-thirds (61.8%wt) were offered prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
146
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 27 publications
6
146
0
Order By: Relevance
“…Moreover, although the evidence is still largely anecdotal, the use of stimulants (particularly those typically prescribed for the treatment of attention-deficit/hyperactivity disorder) as a "countermeasure" to sleepiness and/or as academic "performance enhancers" seems to be an increasingly common phenomenon across college campuses. 85,86 Future investigations need to assess the extent and context of "diversion" of legitimately prescribed stimulant medications as well as the use and abuse of increasingly diverse alternative sources of caffeine (eg, caffeinated alcoholic beverages, candy, foodstuffs). Finally, it should also be noted that both over-the-counter (ie, diphenhydramine) and prescription (ie, zolpidem) medications taken by adolescents to induce sleep may result in residual daytime sleepiness and that commonly used medications (eg, decongestants) and prescription drugs (eg, activating antidepressants [eg, fluoxetine], stimulant medication for attentiondeficit/hyperactivity disorder) may also result in disrupted sleep and consequent daytime sleepiness in adolescents.…”
Section: Other Factors Affecting Sleep In Adolescentsmentioning
confidence: 99%
“…Moreover, although the evidence is still largely anecdotal, the use of stimulants (particularly those typically prescribed for the treatment of attention-deficit/hyperactivity disorder) as a "countermeasure" to sleepiness and/or as academic "performance enhancers" seems to be an increasingly common phenomenon across college campuses. 85,86 Future investigations need to assess the extent and context of "diversion" of legitimately prescribed stimulant medications as well as the use and abuse of increasingly diverse alternative sources of caffeine (eg, caffeinated alcoholic beverages, candy, foodstuffs). Finally, it should also be noted that both over-the-counter (ie, diphenhydramine) and prescription (ie, zolpidem) medications taken by adolescents to induce sleep may result in residual daytime sleepiness and that commonly used medications (eg, decongestants) and prescription drugs (eg, activating antidepressants [eg, fluoxetine], stimulant medication for attentiondeficit/hyperactivity disorder) may also result in disrupted sleep and consequent daytime sleepiness in adolescents.…”
Section: Other Factors Affecting Sleep In Adolescentsmentioning
confidence: 99%
“…Another recent study of students at the same university estimated that 13% of students used cocaine at some point during their 4 years of college (Kasperski et al, 2011). Additionally, nonmedical use of prescription drugs, especially stimulants and analgesics, has received increasing attention recently, and the prevalence appears to vary signifi cantly among campuses (Arria and DuPont, 2010;Ford and Schroeder, 2008;Garnier-Dykstra et al, 2012;McCabe et al, 2007).…”
mentioning
confidence: 99%
“…Among the various prescription stimulants being used nonmedically by adolescents and college students, Adderall (amphetamine aspartate, amphetamine sulfate, dextroamphetamine saccharate, dextroamphetamine sulfate) is the most common (Arria et al, 2008a;Johnston et al, 2012c;Teter et al, 2006). Interestingly, the popularity of nonmedically using prescription stimulants among adolescents and young adults is not only to simply get high but also to help them concentrate and study (Arria et al, 2008a;Garnier-Dykstra et al, 2012;Johnston et al, 2012a;Teter et al, 2006). For instance, 49% of high school seniors who nonmedically used stimulants during the past year indicated that they used these medications to help them study, whereas 36% indicated using stimulants nonmedically to feel good or get high (Johnston et al, 2012a).…”
mentioning
confidence: 99%